Butterfly community composition along a vegetation gradient in the Sierra Chiquita, Mexico - Edmar Meléndez-Jaramillo; Laura Sánchez-Castillo; Juana María Coronado-Blanco; Ma. Teresa de Jesús Segura-Martínez; César Martín Cantú-Ayala (Neotropical Biology and Conservation)
This study compares the variation of richness, abundance, and diversity of butterfly species for vegetation communities along an elevational gradient and during different seasons in the Priority Region for Conservation of Biodiversity, Sierra Chiquita, located in the northeast of Mexico. We also analyze the influence of environmental variables on the abundance and richness of butterfly species. Seven sampling sites were established based on criteria of vegetation distribution per altitudinal gradient. Sampling was on a monthly basis and carried out in six permanent plots at each site, using an aerial entomological net during November 2015 to October 2016. A total of 38,011 specimens, representing six families and 195 species, were collected. All parameter values showed significant differences across sites, except between thorn forest and gallery forest. Seasonality effect was absent on richness and diversity species; however, for species abundance, the differences between dry season and rainy season were significantly different in each site except for the comparison of thorn forest and gallery forest. The association between the environmental variables and butterfly communities in the elevational gradient was significant, being the dew point, the solar radiation, the canopy leaf area, and the number of flowering plants the most important variables. The present work represents an important contribution of the vegetation communities variation in richness, abundance, and diversity of butterflies in the northeast of Mexico. These results highlight the importance of the conservation of this heterogeneous habitat and establish reference data for the diurnal Lepidoptera fauna of the region.